Unveiling Fashion Business, Culture, and Identity in the Most Glamorous Industry - Godart, F.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2012)
Proposing a comprehensive account of the global fashion industry this book aims to present fashion as a social and cultural fact. Drawing on six principles from the industry, Godart guides the reader through the economic, social and political arena of the world's most glamorous industry.
Keywords: Leadership; Marketing; International business enterprises; Arts; Market research; Trade; Business; Commerce; Business Strategy/Leadership.; Marketing; International Business; Arts; Market Research/Competitive Intelligence; Trade